As Implicações das normas sobre terceirização e a reforma trabalhista no âmbito da administração pública: um olhar sobre a vulnerabilidade dos funcionários terceirizados - SILVA, Flávio Ferreira (2021)
The debate about the outsourcing’s Law and the labor’s reform, has a unique contemporaneity in the current Brazilian scenario and it raises many disagreements. Souto Maior (2017, p. 1-2), explains that the defenders of the Labor Reform base their intention on four lines of argumentation: a) modernization of legislation; b) reduce of high labor costs; c) The worker can no longer be treated as a needy person; and d) combat legal uncertainty, and they are still claims that the Reform is necessary to increase the competitiveness of businesses; cease the problem of unemployment; and support small and medium enterprises. Delgado and Delgado (2017, 39-40), in turn, affirm that the Labor Reform clearly emerges to return the Law to its former historical role, that is, an instrument of exclusion, segregation and sedimentation of inequalities between human people and social groups. The research's problem will adress the implications of outsourcing's laws and the labor reform, inclusive, within the scope of Public Administration as well as their effects on labor relations from 2015 to 2017. The objective of this research is to analyze the impacts of outsourcing's laws and labor's reform, including the scope of Public Administration, promoting a panorama about the vulnerability of outsourced employees. Vulnerabilities that add up, in a symbiosis that transposes the concepts, coexisting on the horizon of social and individual human relations in various aspects, is quoted as reference, unpaid legal amounts, which is not only an economic vulnerability, because of the money that the worker did not receive, has social consequences (degradation of living conditions), consequences in the labor (instability to perform the services properly) and judicial reflexes (right of action in the Justice agencies to resolve the situation), all simultaneously and symbiotic, especially with regard to the legal amounts for which the outsourced company is responsible and when this responsibility is removed away from the service acquirer.